Capital injection to banks versus debt relief to households - Jinhyuk Yoo (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
House financing has played a prominent role in advanced economies. In addition, most of the banking crises in advanced economies were associated with boom-bust cycles in house prices. Prominent researchers suggest that more grants for household debt reduction would have provided a significant boost to the economy lacking aggregate demand after the Great Recession of 2007. In contrast, leading policy makers at that time, such as Geithner and Summers, argue differently. In his paper, Yoo comes up with a dynamic stochastic equilibrium (DSGE) model to evaluate the relative effectiveness of a policy to inject capital into banks versus a policy to relieve households of mortgage debt. He concludes that in the middle of a housing debt crisis, when households are highly leveraged, the short-run effects of the debt relief policy are more substantial. When the zero lower bound is additionally considered, the debt relief policy can be much more powerful in boosting the economy both in the short-run and in the long-run.
urn:nbn:de:hebis:30:3-431579
Keywords: E17; E44; E52; E62; G1; G21; H12; 330; capital injection to banks; debt relief to households; housing debt crisis; macro-financial linkages; leverage; zero lower bound